Effect of Work Ecosystem on Employee Performance at the Pamekasan Regency Agency - R. Agoes Kamaroellah; Mohammad Imam Sufiyanto (Ilomata International Journal of Social Science, 2021)
The purpose of this research is to examine the paradigm change of governance implementation. The governance is the implementation of Regional Autonomy which refers to Law No. 32 of 2004 about the performance improvement of autonomous government agencies. It puts the vision, mission, and strategy into actions that confirm the success or failure levels when carrying out activities following the specified programs and policies. There are variables applied to assess the civil servants’ performance achievement. This research focused on the variables that affect the work environment, organizational culture, job satisfaction, and work motivation. The respondents of this research are officials of Echelon III and IV at 14 Autonomous Regional Agencies in the Pamekasan Regency. The number of samples in this study comprised 120 Echelon III and IV officials. Structural Equation Method (SEM) was applied to test the causal relationship between work environment variables, organizational culture, work motivation, job satisfaction, and performance with the aid of the AMOS 20.0 program. The findings indicated (1) the work environment has a significant effect on job satisfaction and performance but has no significant effect on work motivation; (2) organizational culture has a significant impact on job satisfaction and performance but has no significant effect on work motivation; (3) job satisfaction has a significant effect on performance but has no significant effect on work motivation; (4) work motivation has a significant impact on performance but it has no significant effect on work motivation.